2003
DOI: 10.2169/internalmedicine.42.424
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Remission of a Massive CNS Inflammation with Eosinophilic Infiltrate

Abstract: Wereport a case of spontaneousremission of a massive CNSlesion with eosinophilic infiltrate. This 69-yearold man had eosinophilia without any systemic disorder or laboratory evidence of the most common causes of hypereosinophilia. MRIof the brain suggested an infiltrating neoplasm, but histological examination of a nee-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…Our case differed from classical HES because of the spontaneous resolution of eosinophilia and the absence of apparent organ dysfunction. Spontaneous remission of HES has been reported in a patient with brain involvement [6].Another peculiar feature of this case was that the hypereosinophilia was possibly caused by eosinophilopoietic cytokine IL-3. Previous studies have suggested that IL-5 is the principal cytokine inducing eosinophilia in HES [5]; however, the levels of IL-5 are not always increased in affected individuals [4].…”
mentioning
confidence: 60%
“…Our case differed from classical HES because of the spontaneous resolution of eosinophilia and the absence of apparent organ dysfunction. Spontaneous remission of HES has been reported in a patient with brain involvement [6].Another peculiar feature of this case was that the hypereosinophilia was possibly caused by eosinophilopoietic cytokine IL-3. Previous studies have suggested that IL-5 is the principal cytokine inducing eosinophilia in HES [5]; however, the levels of IL-5 are not always increased in affected individuals [4].…”
mentioning
confidence: 60%
“…To date, cellular infiltration into the brain in HES has been verified in three cases (10,13,14). Among these cases, infiltrating cells of the case reported by Battineni et al comprised not only "scattered eosinophils" but also lympho-cytes, histiocytes and plasma cells (14).…”
Section: Discussionmentioning
confidence: 97%
“…However, HES patients with obvious tissue damage should not be observed for 6 months before diagnosis and subsequent treatment (2). In HES, nervous system involvement is sometimes seen and manifests as peripheral neuropathy, recurrent optic neuritis (3), transverse myelitis (4), subdural effusion (5), encephalopathy (6)(7)(8), eosinophilic meningitis (9, 10), benign encephalitis (11,12), mass lesion (10,13,14), brain infarction (6,(15)(16)(17)(18)(19), hemorrhage (6,19), and cerebral venous sinus thrombosis (20,21). The pathogeneses of neurologic dysfunction in HES include [1] direct infiltration of eosinophils into neural tissue, [2] direct secretion of eosinophil products onto neurons or secretion of intracytoplasmic contents into circulation, with subsequent damage to neural tissue, and [3] embolic brain infarction (22).…”
Section: Introductionmentioning
confidence: 99%
“…No published case has previously showed CNS vasculitis. Indeed, we found only four published accounts of HES with any CNS disease that included histopathology [17][18][19][20]. Of these four, one included almost no pathological detail (being principally an MRI study, but mentioning ''reactive gliosis secondary to infarction with abundant intravascular eosinophils'', [19] without vasculitis), and one did not meet the diagnostic criteria for HES (but nonetheless showed no vasculitis) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Various neurological complications have been reported [9][10][11][12][13][14][15], but there are extremely few accounts of CNS pathological changes (and none showing vasculitis) [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%